A multi-port low-power current mode PUF using MOSFET current-division deviation in 65 nm technology. (September 2017) - Li, Gang; Wang, Pengjun; Zhang, Yuejun; Zhang, Huihong
Abstract: Physical unclonable function (PUF) is a promising hardware security primitive for secure key generation and chip identification. This paper proposes a multi-port and low-power PUF based on MOSFET current-division deviation. Owing to the multi-port, it can parallelly generates multi-bit identifications (IDs) in one clock cycle. Moreover, with the MOSFET current-division array operating at sub-threshold region, it displays a low power consumption characteristic. As an embodiment, a 32-port PUF is implemented with full-custom design on 65 nm CMOS process, wherein the layout area and the power dissipation are 35178 µm 2 and 10.3 μW (@1.2 V/100 MHz), respectively. Post-layout simulation results show that it has a high performance in terms of randomness and uniqueness. In addition, it exhibits a worst case reliability of 98.62% over temperature range of – 40 °C to 120 °C and 10% fluctuations in supply voltage, indicating an encouraging reliability and effectiveness.